English Language Education for Graduate Employability in Vietnam - Nghia, Tran Le Huu; Tran, Ly Thi; Ngo, Mai Tuyet (Global Vietnam: Across Time, Space and Community, 2024)
This open access book examines the teaching and learning of English for employability in Vietnamese higher education. Its content is framed within one country to better examine the research issues within the influence of contextual factors. This book investigates how English can contribute to the development of students' employability capitals, particularly in the aspects of human capital, social capital, cultural capital, identity capital, and psychological capital. It presents employers' and employees' perspectives of how and why English is increasingly important for career development. This book is a collection of discussions and viewpoints from teachers, students, and other stakeholders like employers, graduates, and course coordinators on current practices and their proposed improvements to prepare students for their future education, work and life. Based on empirical evidence, this book calls for repositioning English language education within the employability agenda to elevate its status and increase stakeholders' engagement. This book contributes to current debates on advancing the effectiveness of English language education in non-English speaking countries, as a response to internationalization and globalization.